EDUCATIONAL LEADERSHIP STRATEGIES FOR DEVELOPING STUDENTS' INTERESTS AND TALENTS AT SMA NEGERI 1 BARUMUN: AN ISLAMIC EDUCATION PERSPECTIVE - Misdiantri Kurnia; Dian Nisa Istofa; Try Susanti (Edukasi Islami : Jurnal Pendidikan Islam, 2026)
This study examines the strategies employed by the school principal of SMA Negeri 1 Barumun, North Sumatra Province, Indonesia, to develop students' interests and talents, and situates these strategies within the broader objectives of Islamic education. Using a qualitative descriptive approach, data were collected through observation, structured interviews, and document analysis involving the principal, the vice-principal for student affairs, extracurricular supervisors, and students. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña (2014), and validity was established through source, technique, and time triangulation. The findings indicate that the principal implements five interconnected strategies: early identification of students' potential, the creation of a conducive school climate, the strengthening of extracurricular and academic competition programs, the provision of humanistic and personalized guidance, and collaborative engagement with teachers, parents, and external institutions. During the implementation of these strategies, active student participation in extracurricular activities increased from 64% in 2022 to 82% in 2025, and the number of award-winning students rose from 10 to 26 over the same period. Supporting factors include visionary leadership and strong external partnerships, whereas inhibiting factors consist of limited funding, inadequate facilities, and a shortage of specialist supervisors. Read together, the five strategies are interpreted as a holistic model of student development consistent with the objectives of Islamic education, in which academic achievement is integrated with character formation (akhlaq), the actualization of individual potential (fitrah), and social responsibility.